Beyond tokenism - Guldiken, Orhun; Mallon, Mark R.; Fainshmidt, Stav; Judge, William Q.; Clark, Cynthia E. (Strategic Management Journal, 2019)
[Research Summary:We employ an exploratory approach to understand what differentiates boards that retain limited, potentially tokenistic, gender diversity (i.e., a single female director), and boards that more genuinely diversify their composition by appointing additional female directors. Previous studies have speculated that strategic leaders responsible for board appointments may influence this occurrence. Using longitudinal data on U.S. firms, we find that more female top managers and having the sole female director serve on the nominating committee increase the likelihood of additional female director appointments. Boards and nominating committees with younger members amplify these effects, respectively. We use interviews with board members and professional corporate governance consultants to discuss the probable causal mechanisms that underpin these relationships, highlighting novel theoretical insights related to gatekeeping and social psychology. Managerial Summary:We explore what compels firms to appoint additional female directors after the first one, as only one female director could be considered a token. Using data on U.S. firms, we find that more female top managers and having the sole female director serve on the nominating committee make firms more likely to appoint additional female directors. These likelihoods are highest when younger directors make up the board at large and/or nominating committee. Chief executive officers can be change agents for gender diversity in their organizations by hiring female top managers and pushing for better representation of women on boards. Likewise, younger directors appear to enhance board gender diversity. These findings can inform the director selection process.]